ASM Handbook. Volume 1A, - Stefanescu, Doru Michael, 1942- (ASM International, 2017)
Cast iron development engineers, foundry production and support personnel, product-application engineers, and designers now have an ASM Handbook® devoted to the principles, practices, and application of cast iron science and technology. Up-to-date content covers all aspects of cast iron fundamentals and metallurgy, primary and secondary processing, effects of processing on properties, process, and product design, and the engineering properties of specific grades, types, and product forms of iron castings. With emphasis on both the science and applied technology of cast irons, this new ASM Handbook provides specific coverage of many important aspects of cast iron production, analysis, and use. The science of cast iron provides an important foundation on many modern techniques addressed in this new volume, including coverage on computational modeling, computer-aided prediction, and methods of analysis and testing. Also included are articles devoted to important process design factors such as modification and inoculation, effects of trace elements, filling and feeding systems, and the development of solidification microstructures. ASM Handbook, Volume 1A: Cast Iron Science and Technology is an in-depth and comprehensive reference for those who research, develop, process, make, use, analyze, or specify cast irons. Doru M. Stefanescu, Professor Emeritus from The University of Alabama and The Ohio State University, has gathered an international group of leading innovators, researchers, and practitioners in the cast iron field to create an invaluable reference for both practitioners and researchers.--